Serotonergic System Impacts Levodopa Response in Early Parkinson's and Future Risk of Dyskinesia. Issue 2 (22nd October 2020) - Fu, Jessie F.; Matarazzo, Michele; McKenzie, Jessamyn; Neilson, Nicole; Vafai, Nasim; Dinelle, Katie; Felicio, Andre C.; McKeown, Martin J.; Stoessl, A. Jon; Sossi, Vesna
ABSTRACT: Background: The serotonergic system is known to contribute to levodopa‐derived dopamine release in advanced Parkinson's disease. Objective: We investigated the role of the serotonergic system in determining response to treatment in early disease and risk for complications concurrently with dopaminergic alterations. Methods: Eighteen patients with early and stable Parkinson's disease underwent multitracer positron emission tomography using [ 11 C]dihydrotetrabenazine (vesicular monoamine transporter 2 marker), [ 11 C]methylphenidate (dopamine transporter marker), [ 11 C]‐3‐amino‐4‐(2‐dimethylaminomethylphenylsulfanyl)‐benzonitrile (DASB, serotonin transporter marker), and [ 11 C]raclopride (D2 marker) to investigate relationships between striatal dopaminergic and serotonergic alterations and levodopa‐induced dopamine release, related to motor response to treatment and risk for dyskinesias, using a novel joint pattern analysis. Results: The joint pattern analysis revealed correlated spatial patterns conceptually related to abnormal dopamine turnover in the putamen (higher dopamine release associated with dopaminergic and serotonergic denervation); response to treatment significantly inversely correlated with turnover‐related dopamine release ( P  < 10 −5 ). Patterns identified without inclusion of the DASB data showed no correlation with clinical data, indicating an important contribution from the serotonergic system to a clinically relevant abnormal dopamine release in early disease. Subjects who experienced dyskinesia 3 years after baseline scans showed higher turnover‐related dopamine release compared with subjects who remained stable ( P  < 0.01). Conclusions: Joint analysis of dopaminergic and serotonergic data identified a turnover‐related dopamine release component, strongly related to motor response to levodopa in early disease and contributing to higher risk for dyskinesia. These findings suggest that the contribution of the serotonergic system to dopamine release not only increases the risk for motor complications but also fails to provide sustained therapeutic advantage in early disease. © 2020 International Parkinson and Movement Disorder Society